Alkali Metal Species in the Reversible Activation of H2 - Xu, Maotong; Jupp, Andrew R.; Qu, Zheng‐Wang; Stephan, Douglas W. (Angewandte Chemie International Edition, 2018)
MP(tBu)2 (M=Li, Na, K), KH and KN(SiMe3)2 are shown to activate HD reversibly. In the case of MP(tBu)2 this leads to isotopic scrambling and the formation of H2, D2, H(D)P(tBu)2 and MH(D) in C6D6. In toluene, KP(tBu)2 reacts with H2 but also leads to isotopic scrambling into the methyl groups of the solvent toluene. DFT calculations reveal that these systems effect H2 activation via cooperative interactions with the Lewis acidic alkali metal and the basic phosphorus, carbanion, or hydride centres, mimicking frustrated Lewis pair (FLP) behaviour. Mimicking frustration: MP(tBu)2 (M=Li, Na, K) and KN(SiMe3)2 activate HD reversibly. In toluene, KP(tBu)2 also reacts with H2 but leads to isotopic scrambling into the methyl groups of the solvent toluene. DFT calculations reveal that the mechanism mimics frustrated Lewis pair (FLP) behaviour.